Algorithm Theory - SWAT 2010 12th Scandinavian Symposium and Workshops on Algorithm Theory, Bergen, Norway, June 21-23, 2010. Proceedings - Kaplan, Haim. (Lecture Notes in Computer Science,, 2010)
This book constitutes the proceedings of the 12th International Scandinavian Workshop on Algorithm Theory, held in Bergen, Norway in June 2010.